В чистом поле...: рассказы и повести / [вступ. ст. В. Васильева] - Носов Евгений Иванович (1989)
Экземпляры: КХ (20130701) / Инвентарный номер: 947582 / Цена: 2.40 / Сис.шифр: Р2 / Авт.знак: Н 84 / ГРНТИ: 17 / ББК: 84(2)